Endovascular Stenting for Critical Limb Ischemia Patient with Superficial Femoral Artery Occlusive Disease: A Case Report - Mohammad Ryan Ramadhan; Novi Kurnianingsih; Djanggan Sargowo; Cholid Tri Tjahjono (Universitas Brawijaya, 2020)
BACKGROUND: Critical limb ischemia (CLI) is a terminal stage of peripheral arterial disease (PAD), in the absence of intervention, may lead to lower extremity amputation or death. In cases where medical management is not effective or severe cases of PAD, endovascular and surgical interventions are indicated.2 Endovascular interventions become a first-line approach of CLI management and have advanced considerably within the past decade.1,3CASE DESCRIPTION: A 73-year old female with complain of left leg pain, accompanied with necrotic wound since 6 months ago. Duplex ultrasound showed no-flow from proximal to distal left superficial femoral artery (SFA). From CT-Angiography showed total occlusion from proximal left SFA to proximal poplitea artery about 7,2cm with collateral vessels. She was diagnosed with CLI left inferior extremity Fontaine IV Rutherford III. Angiography inferior extrimities was performed with total occlusion from proximal to distal left SFA with collateral vessels run to distal. We deployed a self-expanding stent with size 6mmx100mmx120cm at proximal-mid SFA. The patient showed improvement and was discharged after 5-days observationDISCUSSION: Patients with CLI have high risk of limb-loss without revascularization and high short term risk of cardiovascular events. Endovascular revascularization of femoro-popliteal occlusive offers lower initial risks than open surgery, with grade IIB-recommendation for lesion less than 25cm. Clinical success of endovascular stenting on CLI usually synonymous to limb salvageCONCLUSION:Favorable results can be achieved with endovascular stenting approach in patients with CLI, where close follow-up treatment afterwards can save limb loss.